FTIR, thermal and ionic conductivity studies of nanocomposite polymer electrolytes. Issue 1 (14th September 2018) - Sharma, Shuchi; Pathak, Dinesh; Dhiman, Naresh; Kumar, Rajiv; Kumar, Manoj
Abstract : In this study, proton-conducting nanocomposite plasticized polymer electrolytes based on poly(methyl methacrylate) (PMMA) complexed with trifluoromethanesulfonic acid (HCF3 SO3 ) plasticized with propylene carbonate (PC) and dispersed with nanosized fumed silica (SiO2 ) have been prepared through the solution-casting technique. The ionic conductivity of electrolytes was measured as a function of acid, plasticizer and fumed silica concentrations. A maximum ionic conductivity of 3·31 × 10 −4  S/cm for PMMA + 10 wt% trifluoromethanesulfonic acid polymer electrolytes and 5·37 × 10 −3  S/cm for plasticized polymer electrolytes containing 50 wt% PC has been observed at room temperature. The viscosity percolation threshold for nanocomposite polymer electrolytes was observed at 3 wt% concentration of fumed silica with ionic conductivity of 8·84 × 10 −3  S/cm at room temperature. Fourier transform infrared studies suggested the complexation of constituents of the electrolytes, formation of ion aggregates in unplasticized polymer electrolytes and dissociation of ion aggregates with the addition of the plasticizer in plasticized polymer electrolytes. Differential scanning calorimetry and thermogravimetric analysis studies proved that these electrolytes are thermally stable only up to 130°C. The conductivity shows negligible change with temperature from 30 to 130°C and time of 30 d, which is desirable for their use in practical applications such solid-state batteries, fuel cells, sensors and supercapacitors.